Implementasi Program Penanganan Anak Tidak Sekolah (P-ATS) Bertajuk “Ayo Sekolah Rek” di Desa Sidoharjo Kecamatan Gedeg Kabupaten Mojokerto - Baihakqi, Vaizal; Rahaju, Tjijik (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Quality of education and reduce the dropout rate in Indonesia. Although it has been running, the ideal of education for all has not been achieved. Based on the Regent’s Decree Number 188.45/422/HK/416-012/2023, Sidoharjo Village, Gedeg District, Mojokerto Regency was appointed as one of 8 P-ATS pilot projects. This study uses a qualitative descriptive method with data collection techniques through observation, interviews, documentation, and literature studies. The analysis was carried out based on the Van Meter and Van Horn policy implementation theory which includes six indicators: policy standards and objectives, resources, inter-organizational communication, characteristics of implementers, environment, and implementer disposition. The results of the study indicate that the program standards and objectives are running well and are able to motivate children to return to school. Human resources work according to SOP. However, education to the community is still lacking so that there is a need to increase socialization. The disposition of the implementers is quite good, while communication between organizations needs to be improved even though the budget is limited. The economic, social, and political environment is quite supportive. The researcher suggests that the Mojokerto Regency Government be more active in socializing the program and paying attention to the budget and supporting facilities for P-ATS.